An Overview of Hacking (Trinity Journal of Management, IT & Media (TJMITM), 2010)
The aim of this research project is to  study the detailed research on  hacking, hacking tools & anti  hacking tools by taking hacking  examples. In it we will study the  history behind hacking & the various  types of hackers.  Our aim is basically to study how the  intruders detect the systems &  intrusion scenarios. The paper describes in detail the  various anti hacking tools like  firewalls, encryption, antivirus,  authorization etc.The paper also gives an overview  about passwords & types of  password attacks & also about the  recent Cell Phone Hacking & IT Act  2000.
Keywords: Hacking, Types of Hackers; Hacking Tools; Antihacking Tools